Perry's Handbook Example 13-4 Video Solution - Hariri, M. Hossein (McGraw-Hill's AccessEngineering., 2012)
This video illustrates the distillation of multicomponent light hydrocarbon feed stream. Compute stage temperatures, flow rates, compositions, and reboiler and condenser duties. Sidestream withdrawal. Analysis uses simultaneous numerical converg